2018
DOI: 10.1002/mds.27479
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortical excitability during voluntary inhibition of involuntary tic movements

Abstract: Background: Tics can be voluntarily inhibited. However, the neurophysiology of voluntary tic inhibition remains underexplored. The objective of this study was to explore state‐dependent effects of voluntary tic inhibition on M1 excitability. Methods: Neurophysiological assessments (single motor‐evoked potentials, corticospinal recruitment curves, short‐interval intracortical inhibition, H‐reflex) were performed in 14 adults with Tourette syndrome during voluntary tic inhibition and free ticcing. Regressions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…Moreover, tic expression would have affected the implicit baseline (intertrial intervals) against which task events and hence NoGo and Choose-NoGo contrasts were computed. This intriguing finding of elevated primary motor cortex activity in Tourette syndrome extends transcranial magnetic stimulation data showing heightened primary motor cortex excitability in Tourette syndrome during NoGo states , and greater reduction in primary motor cortex excitability during tic suppression in patients best able to withhold tics (Ganos et al, 2018a). These data also support the hypothesis that tonic regulation of excitability within motor pathways may underlie remission of tics in adolescents whose tics reduce with age , while heightened motor cortex excitability remains in those who express tics into adulthood.…”
Section: Prefrontal Control Of Actionsupporting
confidence: 78%
“…Moreover, tic expression would have affected the implicit baseline (intertrial intervals) against which task events and hence NoGo and Choose-NoGo contrasts were computed. This intriguing finding of elevated primary motor cortex activity in Tourette syndrome extends transcranial magnetic stimulation data showing heightened primary motor cortex excitability in Tourette syndrome during NoGo states , and greater reduction in primary motor cortex excitability during tic suppression in patients best able to withhold tics (Ganos et al, 2018a). These data also support the hypothesis that tonic regulation of excitability within motor pathways may underlie remission of tics in adolescents whose tics reduce with age , while heightened motor cortex excitability remains in those who express tics into adulthood.…”
Section: Prefrontal Control Of Actionsupporting
confidence: 78%
“…135,141 In fact, we have recently demonstrated that volitional inhibitory control over tics reduces corticospinal excitability and that there is a linear relation between an individual patient's capacity to inhibit tics and reduced M1 excitability during tic inhibition (Table 3). 142 Patients with TS and ADHD can have increased ICF when compared with controls, patients with uncomplicated TS patients, and patients with TS with obsessive compulsive disorder 135 ; however, we consider it as a "weak" measure for the differential diagnosis of these conditions.…”
Section: Tourette Syndrome and Other Chronic Tic Disordersmentioning
confidence: 99%
“…Moderate reliability. SICI is associated with greater motor tic severity and presence of ADHD, but it is not affected by voluntary tic inhibition…”
Section: Studies In Which “Canonical” Findings Were Not Confirmedmentioning
confidence: 99%
“…Tics arise when a certain level of hyperexcitability is reached in the motor systems. These models are supported by the neurophysiological results provided by these new articles in which the effective control of tics occurs when there is a decrease in cortical excitability in a situation of voluntary suppression of tics . According to these studies, patients able to at least partially control their tics temporarily superimpose neuro‐compensatory mechanisms dedicated to the control of motor excitability, causing it to decrease.…”
mentioning
confidence: 69%
“…In the current issue of Movement Disorders , two TS studies shed light on the integrity and neurophysiological underpinnings of automatic and voluntary inhibitory motor control and link those mechanisms to tic suppression. Stenner and colleagues provide evidence of preserved automatic inhibition mechanisms in TS, separating them from any compensatory inhibitory control strategy, whereas the results of the study by Ganos and colleagues suggest that effective voluntary suppression of tics is associated with a transient decrease in excitability in the primary motor cortex. Interestingly, the ability to suppress tics is related to the extent of corticospinal suppression in each individual.…”
mentioning
confidence: 99%